2016
DOI: 10.1542/peds.2015-4496
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Exacerbations in Preschoolers With Recurrent Wheeze: A Meta-analysis

Abstract: CONTEXT: Half of children experience wheezing by age 6 years, and optimal strategies for preventing severe exacerbations are not well defined.OBJECTIVE: Synthesize the evidence of the effects of daily inhaled corticosteroids (ICS), intermittent ICS, and montelukast in preventing severe exacerbations among preschool children with recurrent wheeze. LIMITATIONS: More studies are needed that directly compare these strategies. CONCLUSIONS:There is strong evidence to support daily ICS for preventing exacerbations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 45 publications
3
108
0
5
Order By: Relevance
“…A recent Cochrane review found that there was no evidence for maintenance or intermittent montelukast in pre‐school children with EVW. A recent meta‐analysis agreed with these findings, noting the positive effect of intermittent administration of ICS for these children. Previously, an Australian study found a reduction in acute unscheduled medical presentations for those randomised to montelukast compared to placebo …”
supporting
confidence: 55%
“…A recent Cochrane review found that there was no evidence for maintenance or intermittent montelukast in pre‐school children with EVW. A recent meta‐analysis agreed with these findings, noting the positive effect of intermittent administration of ICS for these children. Previously, an Australian study found a reduction in acute unscheduled medical presentations for those randomised to montelukast compared to placebo …”
supporting
confidence: 55%
“…Among medical treatments for control of recurrent preschool wheeze, which are reviewed in this issue by Avraham Beigelman, inhaled corticosteroid use has accrued the most evidence of effectiveness [1821], with less evidence supporting use of leukotriene inhibitors [22]. A recent multicenter randomized crossover trial demonstrated heterogeneity in response to treatment: 74% of 230 children age 12–59 months who require a daily controller medication had a differential response to treatment with daily inhaled corticosteroids, intermittent inhaled corticosteroids, and leukotriene receptor antagonists.…”
Section: Medical Management In Early Childhoodmentioning
confidence: 99%
“…Evidence is accumulating to support the use of modest doses of maintenance inhaled corticosteroid 28. For those infants experiencing severe or frequent episodes, in particular for those requiring critical care, it would seem reasonable to consider an 8-week trial of low dose maintenance inhaled corticosteroids.…”
Section: Maintenance Treatmentmentioning
confidence: 99%